A heart of wisdom : religion and human wholeness - Friedman, Maurice S. (State University of New York Press, 1992)
Annotation Describes religion not as an external creed and form, or as a subjective inspiration, but as a conscious and immediate meeting with ultimate reality. Religion, then, becomes involved with the wholeness of human life; truth appears in the particular and unique as well as in the universal; and duality promotes a separation between spirit and life that neither can survive. Oriented towards Judaism and Christianity. Paper edition (unseen), $16.95. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: Religion.; Religions.; religion (discipline); religions (belief systems, cultures); RELIGION -- Comparative Religion.; RELIGION -- Reference.; Religion; Religions